The Investigation of the Influence of The Gypsy Tribe and The Laugh Seller Gypsy based on Claudio Guillen’s the Aesthetic of Influence Theory - jalil shakeri; rooholah .roozbeh; hamid jafari (مجله مطالعات ایرانی, 2022)
Analyzing the literary works of various nations and discovering the influence relation, enhances the pleasure of their reading and criticism. One of the approaches of comparative studies is the aesthetic of influence which attempts to discover the aesthetic influence of a literary work on other literary and artistic works. The Laugh Seller Gypsy by Ali Akbar Kermaninejad and Zaharia Stancu’s The Gypsy Tribe (1968) inspired by and emanated from gypsies’ culture, and relying on social realism as well, depict a charming and agreeable narration of gypsies’ life. The purpose of the present study is the discovery of mutual influence of two narrative-fictional texts based on Claudio Guillen’s the aesthetic of influence theory. The method of the present study is a documentary-library one by a comparative approach of signs. The outgrowths of the study show that these two novels relying on the basics of social realism possess many similarities in the reflection of cultural, social aspects, customs and manners, and gypsies’ beliefs and life. The corresponding selection of fictional characters, narration and similar plots, the corresponding theme of humiliation and racial discrimination, similar introduction and initial descriptions, corresponding fictional atmosphere and resemblance of the novels’ titles enhance the theory of influence in these novels. Among the discriminating aspects of The Laugh Seller Gypsy by Ali Akbar Kermaninejad are the bold romantic theme, local color, exploitation of stream of consciousness method, the plurality of narrators, bipartite structure and successive flashbacks.